USING EDMODO AND STUDENTS’ READING MOTIVATION ON STUDENTS’ WRITING ABILITY IN NARRATIVE TEXT - Sri Martini; Indawan Syahri; Mulyadi Mulyadi (Esteem Journal of English Education Study Programme, 2021)
Writing ability is the power of students to write something with a good way.  In writing there are some aspects influences in good writing. The aspects are organization, content, grammar, mechanic, and vocabulary.  Besides that, having ideas or opinion also influent in writing activity. The population of the research consisted of all the eighth-grade students of SMP 35 Palembang in the academic year of 2020-2021, and there were 32 students of them chosen as the samples of the research. The samples were selected by using proportional random sampling technique, because all of individuals in the population have the same opportunity to be chosen as the sample. In this research, the researcher investigates the correlation among the the use of edmodo, students’ reading motivation and writing ability. In analyzing the data, it was used multiple correlation in SPSS 22.0 Program for Windows. The data analysis shows that Ryx1x2 = 0,663 at the significant level of 0,05. And for the criteria of significant test is gotten Fcount 9,798 >Ftable (0,05) (4,02). The result of hypothesis test showed that there is a significant correlation among the use of edmodo, students’ reading motivation and writing ability.